1996
DOI: 10.1002/(sici)1097-4636(199602)30:2<193::aid-jbm9>3.0.co;2-m
|View full text |Cite
|
Sign up to set email alerts
|

Resorption of, and bone formation from, new ?-tricalcium phosphate-monocalcium phosphate cements: Anin vivo study

Abstract: Hard cylinders (4.7 x 10 mm) of two kinds of beta-tricalcium phosphate-monocalcium phosphate monohydrate-calcium sulfate hemihydrate (beta-TCP-MCPM-CSH) cements with and without beta-TCP granules (500-1000 microns) were implanted into holes drilled in rabbit femoral condyles for up to 16 weeks. Empty cavities were used as control. Cement resorption and new bone formation in the cylinders were evaluated with contact microradiography and quantified through an automatic image analysis system. At 4 weeks, both kin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
149
0
4

Year Published

1998
1998
2017
2017

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 241 publications
(161 citation statements)
references
References 16 publications
8
149
0
4
Order By: Relevance
“…However, the following values were found: 25.7 ± 0.1 (pH = 7.40), 29.9 ± 0.1 (pH = 6.00), 32.7 ± 0.1 (pH = 5.28) (Ohura et al 1996). The comparative extent of dissolution in acidic buffer is: ACP ) a-TCP ) b-TCP [ CDHA ) HA [ FA (Daculsi et al 1997) (Becker 1989;Rakovan and Pasteris 2015;Cook et al 2005;Dumoulin et al 2011).…”
Section: Geological and Biological Occurrencesmentioning
confidence: 99%
“…However, the following values were found: 25.7 ± 0.1 (pH = 7.40), 29.9 ± 0.1 (pH = 6.00), 32.7 ± 0.1 (pH = 5.28) (Ohura et al 1996). The comparative extent of dissolution in acidic buffer is: ACP ) a-TCP ) b-TCP [ CDHA ) HA [ FA (Daculsi et al 1997) (Becker 1989;Rakovan and Pasteris 2015;Cook et al 2005;Dumoulin et al 2011).…”
Section: Geological and Biological Occurrencesmentioning
confidence: 99%
“…Within bone matrix, calcium is important at the whole tissue level, both as a structural component of the mineralized matrix and as a signal transduction molecule for eliciting cellular responses. Owing to its closed structural resemblance to bones and teeth, HAP has attracted much attention as a substitute material for damaged teeth or bones over the last years (Suchanek and Yoshimura 1997;Hench 1991;Ohura et al 1996).…”
Section: Introductionmentioning
confidence: 99%
“…CPC were well tolerated by the bone cells and could enhance the production of di!erent bone proteins. In vivo experiments on rabbits demonstrated that brushite was resorbed and replaced by newly formed bone within 3 months [2]. During CPC resorption, particle debris were noted around the periphery of the cement [13].…”
Section: Introductionmentioning
confidence: 99%